If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -10) + (x + 40) = 90 Reorder the terms: (-10 + 3x) + (x + 40) = 90 Remove parenthesis around (-10 + 3x) -10 + 3x + (x + 40) = 90 Reorder the terms: -10 + 3x + (40 + x) = 90 Remove parenthesis around (40 + x) -10 + 3x + 40 + x = 90 Reorder the terms: -10 + 40 + 3x + x = 90 Combine like terms: -10 + 40 = 30 30 + 3x + x = 90 Combine like terms: 3x + x = 4x 30 + 4x = 90 Solving 30 + 4x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + 4x = 90 + -30 Combine like terms: 30 + -30 = 0 0 + 4x = 90 + -30 4x = 90 + -30 Combine like terms: 90 + -30 = 60 4x = 60 Divide each side by '4'. x = 15 Simplifying x = 15
| -4+3x+1=5x+2 | | -5-=0 | | -4x-10=7x+23 | | -18=14 | | -x-4y=-3 | | 2(xy+4)=-7 | | (3x-10)+(x+40)=120 | | 6(2b)= | | 3a-8=2(e-4) | | 6x-15-3x=5x-8 | | (3x-10)+(x+40)=60 | | x^2+7x-4x-28= | | -8x+9+4x=41 | | 40m=L | | 5+2x/4=-7x | | 3x+9-1.5x=17-0.5x | | 7b^2+9b=0 | | 11.6=1.5s | | -2x=-12+4x | | -5x-7-x=19 | | -6+1x+1/3 | | -t+5=-t-19 | | 3w+4w=35 | | -18+7a=2a+3+4 | | 3x^3+3x^2=0 | | 6a+10=22a-22 | | 9x-2(x-5)=7(x+1)+9 | | 6x^2-24xy+5xy-20y^2= | | 6a-10=22a-22 | | (2x+4)/6=(2x)/3 | | 6y+2(y-4)=8y-2(y-10) | | n-13=-15 |